Machine learning classification of smoking behaviours: from social environment to the prefrontal cortex - Reinhardt, Pablo; Zacharias, Norman; Fislage, Marinus; Böhmer, Justin; Hollunder, Barbara; Reppmann, Zala; Wiehe, Anton; Rajwich, Rebecca; Dominick, Nanne; Ritter, Kerstin; Bajbouj, Malek; Wienker, Thomas; et al. (Addiction biology, 2025)
The pronounced heterogeneity in smoking trajectories—ranging from occasional or heavy use to successful quitting —highlights substantial interindividual variation within the smoking population. Machine learning is particularly well suited to capture these complex patterns that may be challenging for traditional inferential statistics to uncover. In this study, we applied machine learning to data from a population-based cohort to identify multimodal markers that distinguish smokers from never smokers at baseline and predict long-term cessation success at a 10-year follow-up. We employed 10 times repeated nested cross-validation (10 outer folds, 5 inner folds) to analyse baseline data (T1) from 707 smokers—including 222 heavy smokers (FTND ≥ 4)—and 864 never smokers for smoking status classification. At the 10-year follow-up (T2), we further classified 60 successful quitters (≥ 1 year abstinent) versus 81 non-quitters. Feature importance was assessed using averaged SHAP values derived from test set predictions. Classification models achieved the following performance, expressed by the area under the receiver operating characteristic curve (AUROC; mean ± SD): smokers versus never smokers, 0.85 ± 0.03; heavy smokers versus never smokers, 0.92 ± 0.03; and quitters versus non-quitters, 0.68 ± 0.13. SHAP analysis identified markers of frontal functioning, cognitive control and smoking behaviour within the social environment among the most influential predictors of both smoking status and cessation success. In conclusion, our machine learning analyses support a multifactorial model of smoking behaviour and cessation success, which may inform nuanced risk stratification to advance the development of personalized cessation strategies.